Peranan Karang Taruna Dalam Pembinaan Kewirausahaan Di Kota Cimahi - Salma Salsabila; Muhammad Axsal Satria; Fatimatu Zahro (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
Karang Taruna is a community organization formed under the auspices of the Ministry of Social Affairs has a goal to improve social welfare. In 2020-2024 RPJMN focus was on the development of quality human resources (HR) notice of the phenomenon of demographic dividend and in accordance with a presidential decree No. 12 of 2010 on the National Movement for Mental Revolution with one movement is a movement independent Indonesia. Seeing this, the researchers conducted an analysis of the role of Karang Taruna in RW 31, Melong Tengah Village in fostering entrepreneurship. This study uses descriptive qualitative method that in a descriptive study was not intended to test a particular hypothesis, but only to describe what it is about a variable, symptoms or conditions. Indeed, there are times in this study prove the allegations, but not too prevalent. The common is that descriptive study was not to test the hypothesis (Arikunto, 1993 : 310) with data collection through interviews, observation and documentation to determine the role of Karang Taruna in community development. This study has theoretical and practical benefits. The results of the study showed an entrepreneurial coaching process Kedai 31 runs fine.